Evaluating new simplified assays for harm reduction from methanol poisoning using chromotropic acid kits: An analytical study on Indian and Iranian alcoholic beverages - Ali Rafizadeh; Ashish Bhalla; Neha Sharma; Kuldeep Kumar; Nasim Zamani; Nasim Zamani; Rebecca McDonald; Darren M. Roberts; Darren M. Roberts; Hossein Hassanian-Moghaddam; Hossein Hassanian-Moghaddam (Frontiers Media S.A., 2022)
BackgroundIngestion of methanol can result in severe irreversible morbidity, and death. Simple and easy methods to detect methanol and other hazardous additives prior to consumption can prevent fatalities. This form of harm reduction is analogous to the widely practiced "pill testing" of recreational drugs in various countries. We aimed to evaluate the performance of two qualitative and quantitative kits to simultaneously identify the presence of methanol and formaldehyde in alcoholic beverages, and compare this to the standard gas chromatographic (GC) method.MethodsTwo-hundred samples of Indian and Iranian alcoholic drinks were examined by two new qualitative and quantitative chemical kits designed based on a modified chromotropic acid (CA) method, as well as a gold standard GC method.ResultsMethanol levels were similar when evaluated by GC and quantitative method (Z = - 0.328, p = 0.743). The 75th percentile of methanol level detection was 4,290 mg L−1 (range; 0-83,132) using GC compared to that of 4,671 mg L−1 (range; 0-84,960) using the qualitative kit (predefined color intensity reflecting the methanol/ethanol ratio). The quantitative kit was able to detect all methanol-contaminated and non-contaminated samples (110 and 60 cases, respectively: 100% sensitivity). In 25 samples, GC analysis showed no methanol; but the qualitative kit detected possible toxic substances. Formaldehyde measurement by UV/Vis analysis showed the presence of formaldehyde in 23 samples (92%) with a median 912 [IQR 249, 2,109; range 112-2,742] mg L−1.ConclusionMethanol and formaldehyde can be easily detected using these simple CA chemical kits. Qualitative positive results may indicate the risk of poisoning if the beverage is consumed. CA kits can be used in community setting by public health units and community organizations to monitor for methanol contamination and inform a public health response to reduce methanol-related harms to the public.